Establishment of anti-C1q monoclonal antibodies to measure serum C1q levels discriminating disease severity subsets of rheumatoid arthritis within 5 years of onset. Issue 5 (2nd September 2020) - Yukioka, Chikako; Ebina, Kosuke; Shimaoka, Yasunori; Yukioka, Masao; Yoshikawa, Hideki; Nakata, Ken; Ochi, Takahiro
Abstract: Objectives: To establish anti-C1q monoclonal antibodies which can measure serum C1q levels discriminating disease severity subsets of rheumatoid arthritis (RA) within 5 years of onset. Methods: In this multi-centre, longitudinal, observational study, 122 RA patients [102 females, baseline age 58.5 years, rheumatoid factor (RF) positivity 78.7%, serum C-reactive protein (CRP) 1.2 mg/dl, and concomitant methotrexate (MTX) 4.9 mg/week (29.5%)] within 5 years of onset (disease duration 21.0 months) were enrolled from 1985 to 2000. Patients were not treated by more than 8 mg/week of MTX or biologics which may strongly affect the course of joint destruction. Disease severity at 10–15 years of onset was classified according to the number of destructed joints of overall 68 joints on plain radiographs (36 patients were mild RA group involving only peripheral joints and 86 were severe RA group involving large axial joints). Baseline serum C1q levels were evaluated by ELISA with newly developed 4 monoclonal anti-C1q antibodies, and compared between two groups as well as conventional RA disease activity markers. Results: There were no significant differences between two groups in baseline conventional RA disease activity markers such as RF, erythrocyte sedimentation rate, CRP, and matrix metalloproteinase-3. However, compared to mild RA group, severe RA group showed higher baseline serum C1q levels (μg/ml) evaluated by anti-C1q monoclonal antibodies of no.33 (104.8 ± 22.3 vs. 118.3 ± 19.3; p  = .0024), no. 40 (102.6 ± 21.9 vs 121.2 ± 22.3; p  = .000069), no. 54 (102.1 ± 22.5 vs. 119.3 ± 26.9; p  = .00052), and no. 76 (105.6 ± 21.8 vs. 122.6 ± 26.4; p  = .00043). Receiver operating characteristic curve analysis revealed that in patients with serum C1q levels of ≥110.5 μg/ml (measured by antibody no. 40), 78.9% (75/95) belonged to severe RA group. Conclusion: Measuring serum C1q levels of RA within 5 years of onset by newly developed anti-C1q antibodies may be useful in predicting the prognosis of disease severity evaluated by the extent of joint destruction.